Consideraciones Sobre El Estilo. Estilo Y Estructuras En Tramas Informativas - Osses Macaya, Mario (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
This article is a comparative analysis of two articles published in The Mercury and The Nation, respect of the results of the primary choices (elections) in Iowa that they gave the victory to Barack Obama, for the democratic party, and to Mike Huckabee for the republican party. There are checked the styles and the structures of the informative plots of both means, and how, in the social construction of the reality, the stylistic attributes of each one of these means produce a semantic impact that forms approaches different from the reality.
Keywords: Style; structure; analysis of content; speech; rhetorical resources